EFFECTIVENESS TEST OF ARBUSCULAR MYCORYHZA BIOBERTESTIN ON THE GROWTH OF MATOA SEEDLINGS (Pometia pinnata J.R.FORST. & G.FORST.) IN POST-GOLD MINING SOIL MEDIA - safitri, ikraeni; Supriatna, Supriatna; Puspaningrum, Dian; Dzulhajjah, Rahmah (Universitas Gorontalo, 2025)
Arbuscular Mycorrhiza Fungi (AMF) can be used as a biofertilizer or biological fertilizer so that it increases the absorption of nutrients needed by plants such as P, K, Ca, Mg, Fe. The purpose of this study was to test the effectiveness of the use of arbuscular mycorrhizal fungi fertilizer on the growth of matoa seedlings in post-gold mining soil media. This study used a Randomized Block Design (RAK) with arbuscular mycorrhizal fungi treatment on each plant, including: Control (A), 5 g AMF (B), 10 g AMF (C), 15 g AMF (D). The results showed that the inoculation treatment of 15 g AMF was able to increase the average percentage of root colonization (72.21%), plant height (5.19 cm), diameter (0.80 mm), dry weight of shoots (1.93 g), and seedling quality index (0.26). Therefore, AMF can play a role in increasing the growth of matoa seedlings in nutrient-poor soil, especially post-gold mining soil on a plastic house scale. Therefore, FMA can play a role in increasing the growth of matoa seedlings in nutrient-poor soil, especially post-plastic house-scale gold mining soil.